Land‐use comparison of depression‐focussed groundwater recharge in the Canadian prairies. Issue 9 (24th September 2021) - Morgan, Laura R.; Hayashi, Masaki; Cey, Edwin E.
Abstract: In the cold semiarid Canadian prairies, groundwater recharge is focussed under numerous topographic depressions, in which snowmelt runoff converges. Agricultural land uses on the uplands surrounding the depressions affect snow accumulation, snowmelt infiltration, evapotranspiration (ET) and soil moisture dynamics, thereby influencing snowmelt runoff and depression‐focussed recharge. The objective of this study is to compare the differences in hydrological processes under two common land uses in the Canadian prairies, namely grazed grass and annual crop, and examine how they affect groundwater recharge. A short‐term (3 years) paired catchment study was used for detailed observation of hydrological processes in two depressions, supplemented by a longer‐term (17 years) data set covering a larger scale to quantify the differences in snowmelt runoff between the two land uses. Compared to the grazed grassland, the cropland had a shorter and more intense period of ET, and root water uptake restricted to the shallower (top 0–80 cm) soil zone. The amount of snowmelt runoff was greater in the grazed grassland primarily due to a higher amount of snow accumulation, which was dictated by differences in topography. This finding was contrary to previous studies in the Canadian prairies that indicated substantially smaller snowmelt runoff in ungrazed grassland, but was consistent with the larger‐scale remote sensing results, which showed only a marginal difference between grazed grasslands and croplands. Groundwater recharge rates were estimated using the chloride mass balance method for the present condition using "modern" pore water containing tritium. The rates were similar between the grazed grassland and croplands, implying similarity in snowmelt runoff characteristics. These results suggest that groundwater recharge will continue to be focussed under depressions in the future, though the amount and seasonality of recharge may be influenced by warmer winters. Abstract : In the cold semiarid Canadian prairies, groundwater recharge is focussed under numerous topographic depressions. This study has shown that annual croplands and grazed grasslands have similar snowmelt runoff characteristics despite substantial difference in the seasonality of evapotranspiration and soil moisture dynamics. Groundwater recharge rates were similar between the two land uses, suggesting that the dominance of depression‐focused recharge is unaffected by agricultural land‐use changes.